Impact of Palliative Care Involvement on End-of-Life Care Patterns Among Adolescents and Young Adults With Cancer: A Population-Based Cohort Study. Issue 22 (1st August 2021) - Kassam, Alisha; Gupta, Abha; Rapoport, Adam; Srikanthan, Amirrtha; Sutradhar, Rinku; Luo, Jin; Widger, Kimberley; Wolfe, Joanne; Earle, Craig; Gupta, Sumit
Abstract : PURPOSE: Evidence suggests that adolescents and young adults (AYAs) with cancer (defined as age 15-39 years) receive high-intensity (HI) medical care at the end-of-life (EOL). Previous population-level studies are limited and lack information on the impact of palliative care (PC) provision. We evaluated prevalence and predictors of HI-EOL care in AYAs with cancer in Ontario, Canada. A secondary aim was to evaluate the impact of PC physicians on the intensity of EOL care in AYAs. METHODS: A retrospective decedent cohort of AYAs with cancer who died between 2000 and 2017 in Ontario, Canada, was assembled using a provincial registry and linked to population-based health care data. On the basis of previous studies, the primary composite measure HI-EOL care included any of the following: intravenous chemotherapy < 14 days from death, more than one emergency department visit, and more than one hospitalization or intensive care unit admission < 30 days from death. Secondary measures included the most invasive (MI) EOL care (eg, mechanical ventilation < 14 days from death) and PC physician involvement. We determined predictors of outcomes using appropriate regression models. RESULTS: Of 7, 122 AYAs, 43.8% experienced HI-EOL care. PC physician involvement (odds ratio [OR], 0.57; 95% CI, 0.51 to 0.63) and older age at death (OR, 0.60; 95% CI, 0.48 to 0.74) were associated with a lower risk of HI-EOL care. AYAs with hematologic malignancies were at highest risk for HI and MI-EOL care. PC physician involvement substantially reduced the odds of mechanical ventilation at EOL (OR, 0.36; 95% CI, 0.30 to 0.43). CONCLUSION: A large proportion of AYAs with cancer experience HI-EOL care. Our study provides strong evidence that PC physician involvement can help mitigate the risk of HI and MI-EOL care in AYAs with cancer.